The Incidence, Gender Predilection and Etiology of Sacrococcygeal Pilonidal Sinus - Ahmed Naji Abdalrezaq; Hawar Hassan Naqshbandi; Fadhil Ahmed Mohialdeen; Mohammed IM Gubari (Kurdistan Journal of Applied Research)
Pilonidal Sinus (PNS) is widely distributed in both the emergency department and General Surgery outpatient clinic. Most authors consider the disease as an acquired disease, occurs due to the insertion of broken hairs into the skin with the subsequent tissue inflammation and fibrosis. The incidence of PNS is particularly high in younger males, especially from the Mediterranean region. The aim of the current study was to determine the incidence of the PNS Disease in the city of Sulaimaniyah and the reasons behind the development of the disease. A prospective cohort study was performed in the period between January 2018 and January 2019(1 year) at the Department of Surgery of Shar Teaching Hospital, Sulaimaniyah City. All consecutive patients who presented to the Emergency Department or outpatient clinic and admitted to the Shar Hospital were investigated for the presence of Sacrococcygeal Pilonidal Sinus Disease. Those who found to have the disease were offered surgical excision and examination of the excised specimen for evaluation of the etiology of the Disease. Overall, 103 out of 1000 patients had Pilonidal sinus, while 897 out of 1000 patients did not show any sign of the disease. Fifty-three out of 103 patients with Pilonidal Sinus were symptomatic and the rest were asymptomatic. The factors which associated with the presence of PNS were: family history (23/103 compared with 45/897, p < 0.0001); overweight defined as BMI > 25 (39/103 compared with 213/897, p < 0.0001); having excessive body hair distribution (41/103 compared with 122/897, p < 0.05). PNS is considered one of the acquired clinical conditions, that is occurred due to insertion of a hair shaft into the skin, followed by subsequent local inflammation and granulation tissue formation. If the etiology is clearly identified, the condition can be readily prevented.